A contribution of fishermen's wives in increasing income: contribution of fishermen's wives in increasing income - Anita Indrianingsih; Heminuddin; Purnamasari, Elly (2339-1324, 2024)
ABSTRAK Anita Indrianingsih, 2023.Fisherman's Wife's Contribution In Increasing Family Income In Kolo Village, Asakota District Bima City west Nusa Tenggara. (Supervised by Helminuddin and Elly) Purnamasari